Konsep Pengelolaan Harta Wakaf Dalam Perspektif Syekh Ahmad Khatib Al-Minangkabawi - Afif Aulia Novirman (Jurnal Ilmiah Ekonomi Islam, 2023)
One of the purposes of waqf is to get the benefit and welfare of the people. One type of waqf is waqf ahli, namely waqf, which is addressed to the closest family. One of the influential ulama figures in Minangkabau is Sheikh Ahmad Khatib Al-Minangkabawi. He is the Imam of the Grand Mosque in Makkah and derivered his though to students in indonesia, one of which is Abdul Karim Amrullah (HAMKA's father). Syekh Ahmad Khatib, in his preaching, always prioritizes Islamic law. One of the works that are being debated in Minangkabau is the law of inheritance in Minangkabau. In the book, inheritance law which is implemented based on Minangkabau customary law is not valid. Therefore, many traditional leaders disagreed with Syekh Ahmad Karim's opinion. This type of research is literature research where the sources come from journal literature and books. The purpose of this study was to reveal and analyze the perspective of Syekh Ahmad Khatib Al-Minangkabawi from the perspective of expert or family endowments in Minangkabau and to reveal the opinions of scholars in Minangkabau about expert waqf law in Minangkabau.